(untitled) (REMUNOM, 2024)
Introduction: the leukemia is a malignant disease of the bone marrow and blood and represents the most common pediatric neoplasm. In addition to compromising the general health of the leukemic child, this condition causes oral manifestations resulting from the disease itself and/or its treatment. Objective: to carry out a literature review on the main oral manifestations observed in pediatric leukemic patients. Methodology: a bibliographic survey was carried out with articles indexed in the Pubmed/Medline and Lilacs databases, during the period from 2012 to 2024, using the descriptors: “leukemia”, “child”, “mouth diseases” and “oral health”. After careful analysis, 13 scientific productions were selected to compose this review. Results: the studies reviewed indicated that oral manifestations such as oral mucositis, dental caries, gingival changes, salivary changes and opportunistic infections were more frequently found in pediatric patients with leukemia when compared to healthy children. Conclusion: it was possible to infer that leukemia is a complex disease with diverse repercussions for the affected organism. In this review, oral mucositis was the oral manifestation most frequently reported in the literature in pediatric patients and can often be accompanied by dental caries, periodontal problems, salivary changes and opportunistic infections. It was found that such conditions, in turn, can occur as complications of the disease and/or adverse effects of antineoplastic therapy. Keywords: Leukemia; child; oral manifestations.